Two simple image slicers for high resolution spectroscopy - Tala, Marcelo (Experimental astronomy, 2017)
We present the design, manufacturing, test and performance of two image slicers for high resolution spectroscopy. Based on the classical Bowen-Walraven concept, our slicers allow to make two slices of the image of the input fibre. We introduce the idea of a second fibre that can be cropped in half to reach the same width of the science target fibre and that can be used for simultaneous wavelength reference. The slicers presented are mirror and prism based, respectively. Both devices work within expectation, showing differences mainly in their efficiency. The prism based slicer is the solution that was adopted for the FIDEOS spectrograph, an instrument built by the AIUC for the ESO 1m telescope of La Silla. Test spectra obtained with this instrument are included as examples of a real application of the device.